Afirmarea principiului neintervenției ca principiu fundamental al dreptului internațional [Articol] - Vieru, Grigore (CEP USM, 2019)
Interzicerea intervențiilor în viața altor națiuni sau state nu este doar o concluzie ce derivă din principiile care stau la temelia dreptului internațional public, ci reprezintă un principiu fundamental al neimixtiunii. Acest principiu asigură securitatea ca fiecare națiune sau stat să fie stăpân pe soarta sa. Pentru o mai bună dezvoltare a societății în relațiile dintre state nu trebuie să fie utilizat limbajul forței, presiunea și amenințarea pentru a impune voința unei națiuni alteia, ci trebuie ca relațiile internaționale să fie bazate pe respectul fiecărui stat și al fiecărei națiuni.

The implementation of the non-interference principle within public international law arose as a condition for maintaining peace within and between nations, this condition stems from a long historical process to achieve a peaceful world. This principle assures each nations and states' right to pursue its own destiny and to take charge in safeguarding it's own security or a continuous development of societies around the world, relationships between states need to be free of languages implying force, pressure and threats purposefully imposing one state's will over another. This means, that relationships between nations and states should be based on continuous respect of any state or nation, with no exceptions.
UNDERSTANDING THE PRINCIPLE OF NON-INTERVENTION AS A FUNDAMENTAL PRINCIPLE OF INTERNATIONAL LAW
Keywords: suveranitate; stat; securitate mondială